Method for manufacturing secondary battery electrodes

By first forming the first and second electrode layers in the secondary battery electrode manufacturing and applying an electrolyte on the surface of the electrode layer before pressing, the electrode layer density control problem is solved, the battery capacity and charging speed are improved, and the electrode layer is efficiently stacked and continuous production are achieved.

JP7626123B2Active Publication Date: 2025-02-04TOYOTA JIDOSHA KK
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2022178380
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2022-11-07
Publication Date
2025-02-04
Estimated Expiration
2042-11-07

AI Technical Summary

Technical Problem

In the prior art, when manufacturing secondary battery electrodes, the compression of the positive and negative electrode layers makes it difficult to control the density, affecting the adhesion between the electrode layer and the current collector, thereby reducing the battery capacity and fast charging performance.

Method used

By first forming the first electrode layer and the second electrode layer, each layer is ensured to achieve the desired density and continuous manufacturing using an intermediate transport body by applying an electrolyte on the surface of the electrode layer and separation of the electrode layers before pressing.

Benefits of technology

The adhesion between the electrode layer and the substrate is improved, the capacity and fast charging performance of the battery are enhanced, and efficient stacking and continuous production of the electrode layer are achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007626123000001
    Figure 0007626123000001
  • Figure 0007626123000002
    Figure 0007626123000002
  • Figure 0007626123000003
    Figure 0007626123000003
Patent Text Reader

Abstract

To provide a manufacturing method of an electrode for secondary batteries capable of improving adhesiveness between an electrode layer and a substrate and improving a battery capacity and quick chargeability.SOLUTION: A manufacturing method of an electrode for secondary batteries includes: a step (S10) of forming a first electrode layer with a first density on a first principal surface of a first substrate; a step (S20) of preparing a second electrode layer which is formed with a second density; a step (S40) of laminating the prepared second electrode layer on a second principal surface of the first substrate; and a step (S30) of coating at least one of the second principal surface of the first substrate and a surface of the second electrode layer in contact with the second principal surface with an electrolyte prior to the step (S40) of laminating the second electrode layer.SELECTED DRAWING: Figure 2
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a method for producing an electrode for a secondary battery. [Background technology]

[0002] As a conventional method for manufacturing electrodes for secondary batteries, Japanese Patent Publication No. 7008813 (Patent Document 1) discloses a method for manufacturing a bipolar electrode by applying a positive electrode mixture slurry to a predetermined area on a first surface of a current collector, applying a negative electrode mixture slurry to a predetermined area on a second surface of the current collector, arranging an electrical insulating member on the outer periphery of the negative electrode mixture slurry, and then pressing the positive electrode mixture slurry, negative electrode mixture slurry, and electrical insulating member together. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] Patent No. 7008813 Summary of the Invention [Problem to be solved by the invention]

[0004] However, as described in Patent Document 1, when the positive electrode mixture slurry constituting the positive electrode layer and the negative electrode mixture slurry constituting the negative electrode layer are pressed together, the electrode layer which is more easily compressed of the positive electrode layer and the negative electrode layer is pressed preferentially.

[0005] This makes it difficult to form the positive electrode layer and the negative electrode layer at a desired density, and the adhesion between the positive electrode layer and the negative electrode layer and the current collector may decrease. In such a case, it becomes difficult to improve the battery capacity and rapid chargeability, and there is a concern that the reliability may also decrease due to the decreased adhesion.

[0006] The present disclosure has been made in consideration of the above-mentioned problems, and an object of the present disclosure is to provide a method for manufacturing an electrode for a secondary battery that can increase adhesion between an electrode layer and a substrate and improve battery capacity and rapid chargeability. [Means for solving the problem]

[0007] A method for manufacturing an electrode for a secondary battery based on the present disclosure includes the steps of forming a first electrode layer at a first density on a first main surface of a first substrate, preparing a second electrode layer formed at a second density, stacking the prepared second electrode layer on the second main surface of the first substrate, and applying an electrolyte solution to at least one of the second main surface of the first substrate and a surface of the second electrode layer that will be in contact with the second main surface prior to the step of stacking the second electrode layer.

[0008] According to the above configuration, the first electrode layer and the second electrode layer, each formed with a desired density, can be laminated on the first main surface and the second main surface of the first substrate. This allows for high capacity and improved high-speed charging performance. In addition, by applying an electrolyte solution to at least one of the second main surface of the first substrate and the surface of the second electrode layer before laminating the second electrode layer on the first substrate, the adhesion of the second electrode layer to the first substrate can be increased by the liquid bridging force.

[0009] In the method for manufacturing a secondary battery electrode according to the present disclosure, the step of preparing the second electrode layer may include a step of forming the second electrode layer on a surface of a second substrate, and a step of pressing the second electrode layer formed on the surface of the second substrate. The step of stacking may include a step of peeling the second electrode layer from the second substrate.

[0010] According to the above configuration, the second electrode layer can be formed to the second density by pressing the second electrode layer before laminating it on the first substrate, and the second electrode layer peeled off from the second substrate can be laminated on the first substrate.

[0011] In the method for manufacturing a secondary battery electrode according to the present disclosure, an endless intermediate transfer body may be used as the second substrate, and in this case, the step of laminating the second electrode layer may include a step of transferring the second electrode layer from the intermediate transfer body to the second main surface of the first substrate.

[0012] According to the above-mentioned configuration, secondary battery electrodes can be continuously manufactured while highly precisely controlling the lamination position of the second electrode layer.

[0013] In the method for manufacturing an electrode for a secondary battery based on the present disclosure, a first transport speed for transporting the first substrate on which the first electrode layer is formed toward a transfer position at which the second electrode layer is transferred may be faster than a second transport speed for transporting the intermediate transfer body on which the second electrode layer is formed toward the transfer position.

[0014] According to the above configuration, the shapes of the first electrode layer and the second electrode layer after lamination can be well maintained.

[0015] In the manufacturing method for an electrode for a secondary battery based on the present disclosure, the first substrate may be a bonded body in which a first metal foil constituting the first main surface and a second metal foil constituting the second main surface are bonded together.

[0016] According to the above configuration, a first electrode layer is formed on the first metal foil of the joined body, and a second electrode layer is laminated on the second metal foil of the joined body, thereby making it possible to manufacture an electrode for a secondary battery.

[0017] In the method for producing an electrode for a secondary battery according to the present disclosure, the first electrode layer and the second electrode layer may have different polarities.

[0018] According to the above-mentioned configuration, it is possible to manufacture a bipolar electrode that can enhance the adhesion between the electrode layer and the substrate, and can improve the battery capacity and rapid chargeability. Effect of the Invention

[0019] According to the present disclosure, it is possible to provide a method for manufacturing an electrode for a secondary battery that is capable of increasing the adhesion between an electrode layer and a substrate and improving battery capacity and rapid chargeability. [Brief description of the drawings]

[0020] [Figure 1] 1 is a cross-sectional view showing an electrode for a secondary battery according to an embodiment. [Diagram 2] FIG. 2 is a flow diagram showing a manufacturing process of an electrode for a secondary battery according to an embodiment. [Diagram 3] 3 is a diagram showing a step of forming a first electrode layer on a first main surface of a first base material in the manufacturing process shown in FIG. 2. FIG. [Figure 4] 3A to 3C are diagrams showing steps in the manufacturing process shown in FIG. 2, from the formation of a first electrode layer until the lamination of a second base material on a first base material. [Diagram 5] FIG. 1 is a diagram showing the conditions and results of a verification experiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0021] Hereinafter, embodiments of the present disclosure will be described in detail with reference to the drawings. In the embodiments described below, the same or common parts are denoted by the same reference characters in the drawings, and the description thereof will not be repeated.

[0022] 1 is a cross-sectional view showing an electrode for a secondary battery according to an embodiment of the present invention, with reference to which an electrode 100 for a secondary battery according to the embodiment of the present invention will be described.

[0023] The electrode 100 is, for example, a bipolar electrode. The electrode 100 includes a first substrate 10, a first electrode layer 21, and a second electrode layer 22.

[0024] The first base material 10 has a first main surface 10a located on one side in the stacking direction, and a second main surface 10b located on the other side in the stacking direction.

[0025] The first base material 10 is composed of a bonded body in which a first metal foil 11 and a second metal foil 12 are bonded together. The first metal foil 11 and the second metal foil 12 are bonded together by an adhesive layer 13 interposed therebetween.

[0026] The first metal foil 11 constitutes the first main surface 10a. The first metal foil 11 is, for example, a negative electrode current collector. The first metal foil 11 may contain at least one selected from the group consisting of stainless steel, copper (Cu), Ni, Fe, Ti, cobalt (Co), and Zn. The first metal foil 11 is, for example, formed of a metal member such as a copper foil.

[0027] The second metal foil 12 constitutes the second main surface 10b. The second metal foil 12 is, for example, a positive electrode current collector plate. The second metal foil 12 may contain at least one selected from the group consisting of aluminum (Al), stainless steel, nickel (Ni), chromium (Cr), platinum (Pt), niobium (Nb), iron (Fe), titanium (Ti), and zinc (Zn). The metal foil is, for example, formed of a metal member such as an Al foil.

[0028] The first electrode layer 21 is formed on the first main surface 10a. The first electrode layer 21 is, for example, a negative electrode active material layer. The density of the first electrode layer 21 is, for example, 1.2 g / cm 3 By setting the density in this range, it is possible to improve the rapid charging performance. The negative electrode active material layer includes a negative electrode material and a binder.

[0029] The negative electrode active material may be, for example, a carbon-based negative electrode active material such as graphite, graphitizable carbon, or non-graphitizable carbon, or may be an alloy-based negative electrode active material containing silicon (Si), tin (Sn), etc. The binder may contain, for example, at least one selected from the group consisting of PVdF and vinylidene fluoride-hexafluoropropylene copolymer (PVdF-HFP).

[0030] The second electrode layer 22 is formed on the second main surface 10b. The second electrode layer 22 has an opposite polarity to the first electrode layer 21. The second electrode layer 22 is, for example, a positive electrode active material layer. The density of the second electrode layer 22 is, for example, 3.3 g / cm 3 By setting the density in this range, it is possible to increase the capacity. The density of the second electrode layer 22 is higher than the density of the first electrode layer 21.

[0031] When viewed from the stacking direction, the size of the second electrode layer 22 is larger than the first electrode layer 21. This makes it possible to suppress the formation of dendrites on the second electrode layer 22 side, and suppress the deterioration of battery performance.

[0032] The positive electrode active material layer includes a positive electrode active material and a conductive material. In the present embodiment, the positive electrode active material layer does not include a binder because an electrolyte is applied to the positive electrode active material layer in the manufacturing process as described later.

[0033] The positive electrode active material may be, for example, lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, or lithium nickel cobalt manganese oxide (e.g., LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2, etc.), lithium nickel cobalt aluminate, and lithium iron phosphate.

[0034] The conductive material may include, for example, at least one selected from the group consisting of carbon black (such as acetylene black), vapor grown carbon fiber (VGCF), carbon nanotubes (CNT), and graphene flakes.

[0035] 2 is a flow diagram showing the steps of manufacturing the secondary battery electrode according to the embodiment. A method of manufacturing the secondary battery electrode 100 according to the embodiment will be described with reference to FIG.

[0036] As shown in FIG. 2, the method for manufacturing an electrode 100 for a secondary battery includes a step of forming a first electrode layer (S10), a step of preparing a second electrode layer (S20), a step of applying an electrolytic solution (S30), and a step of stacking the second electrode layer (S40).

[0037] FIG. 3 is a diagram showing a step of forming a first electrode layer on a first main surface of a first base material in the manufacturing process shown in FIG.

[0038] 2 and 3, in manufacturing the electrode 100, in step (S10), a first electrode layer 21 is formed on a first main surface 10a of a first substrate 10. Specifically, for example, using an electrostatic screen device 30, the first electrode layer 21 is formed on the first main surface 10a of the first substrate 10 supplied from a supply roller 41. The first substrate 10 is a bonded body in which the first metal foil 11 and the second metal foil 12 are bonded together as described above.

[0039] The electrostatic screening device 30 includes a mixing tank 31, a supply unit 32, and a screen 33. In the mixing tank 31, the above-mentioned negative electrode composite material and binder are mixed to form a negative electrode composite. The negative electrode composite discharged from the mixing tank 31 is supplied to the screen 33 by the supply unit 32. The supply unit 32 is composed of a roller, and the screen 33 is composed of a metal mesh.

[0040] The negative electrode composite pushed out of the mesh by the roller moves toward the first main surface 10a by an electrostatic field generated between the screen 33 and a support table (not shown) that supports the first substrate 10. As a result, the first electrode layer 21 is formed on the first main surface 10a. Next, the first substrate 10 on which the first electrode layer 21 is formed is transported so as to pass between a pair of press rollers 43, 44. At this time, the first electrode layer 21 is sandwiched and pressed by the pair of press rollers 43, 44 at a predetermined temperature (for example, about 160°C). As a result, the binder melts, and the first electrode layer 21 is adhered to the first main surface 10a and formed with a desired first density.

[0041] The member for pressing the first electrode layer 21 is not limited to a pair of rollers, and may be a pair of flat plates or the like.

[0042] FIG. 4 is a diagram showing each step in the manufacturing process shown in FIG. 2, from the formation of the first electrode layer until the lamination of the second base material on the first base material.

[0043] 2 and 4, in step (S20), a second electrode layer 22 formed at a second density is prepared. Specifically, first, in step (S21), the second electrode layer 22 is formed on a surface 60a of a second substrate 60. The second substrate 60 is, for example, an endless intermediate transfer body, and is wound around a first roller 61 and a second roller 62.

[0044] When forming the second electrode layer 22, an electrostatic screening device 50 is used. The electrostatic screening device 50 includes a mixing tank 51, a supply unit 52, and a screen 53. In the mixing tank 51, the above-mentioned positive electrode material and conductive material are mixed to form a positive electrode composite. The positive electrode composite discharged from the mixing tank 51 is supplied to the screen 53 by the supply unit 52. The supply unit 52 is composed of a roller, and the screen 53 is composed of a metal mesh.

[0045] The positive electrode composite pushed out from the mesh by the roller is moved toward the surface 60 a of the second substrate 60 by an electrostatic field generated between the screen 53 and a support table (not shown) that supports the second substrate 60 .

[0046] Next, in step (S22), the second electrode layer 22 formed on the surface 60a of the second base material 60 is pressed. Specifically, the second electrode layer 22 is sandwiched and pressed between a first roller 61 and an opposing roller 63. The opposing roller 63 is disposed so as to face the first roller 61 in a direction intersecting the direction in which the first roller 61 and the second roller 62 are arranged side by side.

[0047] The second substrate 60 is transported by the rotation of the first roller 61 and the second roller 62, and the second electrode layer 22 formed on the surface 60a of the second substrate 60 passes between the first roller 61 and the opposing roller 63. At this time, the second electrode layer 22 is pressed by the first roller 61 and the opposing roller 63 and formed to the second density. The second electrode layer 22 formed to the second density is transported toward a lamination position P (transfer position). The lamination position P is located downstream in the transport direction from the pressing position of the second electrode layer 22 (the nip portion between the first roller 61 and the opposing roller 63).

[0048] Similarly, the first substrate 10 on which the first electrode layer 21 having the first density is formed is transported toward the stacking position P. The first substrate 10 is transported by a transport roller 71. The transport roller 71 is disposed opposite the first roller 61 so that the stacking position P is located between the transport roller 71 and the first substrate 10. The first substrate 10 is transported so that, at the stacking position P, the second main surface 10b faces the first roller 61 and the first main surface 10a faces the transport roller 71.

[0049] Next, in step (S30), before laminating the second electrode layer 22 on the second main surface 10b of the first substrate 10, an electrolyte is applied to at least one of the second main surface 10b of the first substrate 10 and the surface 22a of the second electrode layer 22 that will be in contact with the second main surface 10b.

[0050] As the electrolyte, for example, a lithium-containing solvent is used. Specifically, the electrolyte is obtained by dissolving an electrolyte salt in an organic solvent. Examples of the organic solvent include esters such as propylene carbonate, ethylene carbonate, and γ-butyl lactone, ethers such as diethyl ether, tetrahydrofuran, substituted tetrahydrofuran, dioxolane, pyran and its derivatives, dimethoxyethane, and diethoxyethane, 3-substituted 2-oxazolidinones such as 3-methyl-2-oxazolidinone, sulfolane, methylsulfolane, acetonitrile, and propionitol, which can be used alone or in a mixture of two or more kinds.

[0051] As the electrolyte salt, lithium salts such as lithium perchlorate, lithium fluoroborate, lithium phosphofluoride, lithium chloroaluminate, lithium halide, and lithium trifluoromethanesulfonate can be used.

[0052] The application of the electrolyte solution is performed by an electrolyte solution application device 80. The electrolyte solution application device 80 may be, for example, a die coater.

[0053] Next, in step (S40), a second electrode layer 22 is laminated on the second main surface 10b of the first substrate 10. Specifically, in step (S41), the second electrode layer 22 is peeled off from the second substrate 60, and in step (S42), the second electrode layer 22 peeled off from the second substrate 60 is laminated on the first substrate 10.

[0054] In the present embodiment, step (S41) and step (S42) are performed almost simultaneously. Specifically, when the first substrate 10 and the second electrode layer 22 pass between the first roller 61 and the transport roller 71, the second electrode layer 22 is sandwiched between the first roller 61 and the transport roller 71 while being transported. At this time, the second electrode layer 22 is peeled off from the second substrate 60, and the surface 22a of the second electrode layer 22 comes into contact with the second main surface 10b of the first substrate 10.

[0055] As described above, the electrolytic solution is applied to at least one of the surface 22a and the second main surface 10b of the second electrode layer 22. Therefore, the second electrode layer 22 adheres closely to the second main surface 10b due to a liquid bridging force. In addition, the second electrode layer 22 is sandwiched between the first roller 61 and the transport roller 71, so that the second electrode layer 22 is laminated (transferred) onto the second main surface 10b.

[0056] Through these steps, the electrode 100 can be manufactured. When the second electrode layer 22 is transferred using a transfer method, the electrode 100 can be continuously manufactured while highly precisely controlling the lamination position of the second electrode layer 22.

[0057] The first transport speed at which the first base material 10 on which the first electrode layer 21 is formed is transported toward the transfer position (stacking position P) where the second electrode layer 22 is transferred is faster than the second transport speed at which the second base material 60 on which the second electrode layer 22 is formed is transported toward the transfer position. This makes it possible to maintain good shapes of the first electrode layer 21 and the second electrode layer 22 after stacking.

[0058] As described above, according to the method for manufacturing an electrode for a secondary battery in this embodiment, the first electrode layer and the second electrode layer, each formed with a desired density, can be laminated on the first main surface 10a and the second main surface 10b of the first substrate 10. This allows for high capacity and improved high-speed charging performance. In addition, before laminating the second electrode layer 22 on the first substrate 10, an electrolyte solution is applied to at least one of the second main surface 10b of the first substrate 10 and the surface 22a of the second electrode layer 22, thereby increasing the adhesion of the second electrode layer 22 to the first substrate 10 by the liquid bridging force.

[0059] [Verification experiment] 5 is a diagram showing the conditions and results of the verification experiment. The verification experiment will be described with reference to FIG.

[0060] 5, in the verification experiment, the electrode according to Example 1 and the electrodes according to Comparative Examples 1 and 2 were prepared. Secondary batteries were manufactured using the electrode according to Example 1 and the electrodes according to Comparative Examples 1 and 2, and the input / output performance, rapid charging performance, and energy density were evaluated.

[0061] In the evaluation of input / output performance, a small cell of about 45 mm×47 mm was created with a monopolar structure, and the IV resistance was measured. The resistance values ​​(mΩ) obtained in Example 1 and Comparative Examples 2 and 3 were compared in ratio.

[0062] In evaluating the rapid charging performance, the rapid charging performance was calculated from the physical properties of the produced electrodes using 1D simulation (Newman model simulation).

[0063] The energy density was evaluated by calculation from the physical property values ​​of the produced electrodes using the following relational expressions (1) to (5).

[0064] Energy density (Wh / L) = cell capacity (Wh) / cell volume (L) Equation (1) Cell capacity (Wh) = capacity (Ah) × average voltage (V) Equation (2) (*The average voltage is determined by the type of active material.) Capacity (Ah) = active material ratio (%) x basis weight (mg / cm 2 ) × number of layers × active material charge capacity (mAh / g) × initial coulomb efficiency (%) / electrode area (mm 2 )...Equation (3) Cell volume = electrode area × total thickness Equation (4) Number of layers = total thickness / thickness of each cell... Equation (5)

[0065] Example 1 The electrode according to Example 1 was manufactured using the manufacturing method of a secondary battery electrode in this embodiment. The second electrode layer 22 used did not contain a binder. The positive electrode active material and conductive material contained in the second electrode layer 22 were NCM (lithium nickel cobalt manganese oxide) and acetylene black, respectively. In this case, the ratio of the positive electrode active material and conductive material (positive electrode active material / conductive material) was 95 / 5 (wt%).

[0066] The negative electrode active material and binder contained in the first electrode layer were amorphous coated graphite and PVdF, respectively, with the ratio of the negative electrode active material and binder (negative electrode active material / binder) being 97.5 / 2.5 (wt%).

[0067] In the first base material 10, a Cu foil was used as the first metal foil 11. The thickness of the Cu foil was about 10 μm. An Al foil was used as the second metal foil 12. The thickness of the Al foil was about 40 μm. The thickness of the adhesive layer 13 was about 3 μm.

[0068] Based on the above-mentioned step (S10), the first electrode layer 21 was formed on the first main surface 10a of the first substrate 10. At this time, the basis weight was about 22.6 mg / cm 2 The first density is 1.2 mg / cm 3 The first electrode layer 21 was formed so as to have the following dimensions. The size of the first electrode layer 21 was about 60 mm wide x 200 mm long.

[0069] Based on the above-mentioned step (S20), the second electrode layer 22 was formed on the second substrate 60. At this time, the basis weight was about 38 mg / cm 2 The second density is 3.3 mg / cm 3 The second electrode layer 22 was formed so as to have the following dimensions: The size of the second electrode layer 22 was approximately 56 mm wide x 196 mm long.

[0070] Based on the above-mentioned step (S30), solulite was applied as an electrolyte to surface 22a of second electrode layer 22 or second main surface 10b of first substrate 10.

[0071] Based on the above-mentioned step (S40), the second electrode layer 22 was laminated (transferred) onto the second main surface 10b of the first substrate 10 so that the second electrode layer 22 was positioned inside the area corresponding to the area in which the first electrode layer 21 was formed.

[0072] At this time, the transport speed of the first substrate 10 was about 1.0 mm / min, and the transport speed of the second substrate 60 was about 0.7 mm / min. The transfer pressure when transferring the second electrode layer 22 was about 2 kN.

[0073] In Example 1, the resistance value of the input / output performance was set to 100%. The quick charging performance was 28 minutes, which was a good result. The energy density was 583 Wh / L, which was also a good result. The overall evaluation was that a good electrode was formed.

[0074] (Comparative Examples 1 and 2) The electrodes according to Comparative Examples 1 and 2 are different from the electrode according to Example 1 in that a second electrode layer 22 containing a binder is used, and in that the manufacturing process is different.

[0075] NCM (nickel cobalt lithium manganese oxide), acetylene black, and PVdF were used as the positive electrode active material, conductive material, and binder, respectively, contained in the second electrode layer 22 in Comparative Examples 1 and 2. In this case, the ratio of the positive electrode active material, conductive material, and binder (positive electrode active material / conductive material / binder) was 95 / 5 / 5 (wt%).

[0076] In the manufacturing process of the electrodes in Comparative Examples 1 and 2, the first electrode layer 21 and the second electrode layer 22 were formed on the first principal surface 10a and the second principal surface 10b, respectively, without applying an electrolyte solution, and then the first electrode layer 21 and the second electrode layer 22 were pressed together.

[0077] Specifically, in manufacturing the electrodes according to Comparative Examples 1 and 2, first, the first electrode layer 21 was formed on the first main surface 10a of the first base material 10 by using an electrostatic screen method, and then the first electrode layer 21 was pressed at a temperature of about 160° C. and with a predetermined pressure. This caused the binder contained in the first electrode layer 21 to melt, and the first electrode layer 21 was fixed to the first main surface 10a.

[0078] Next, the second electrode layer 22 was formed directly on the second main surface 10b of the first base material 10 using an electrostatic screen method, and then the second electrode layer 22 was pressed at a temperature of about 160° C. and a predetermined pressure. This caused the binder contained in the second electrode layer 22 to melt, and the second electrode layer 22 was fixed to the second main surface 10b.

[0079] Next, the first electrode layer 21 and the second electrode layer 22 were densified together by roll pressing. At this time, the pressing pressure was changed between Comparative Example 1 and Comparative Example 2.

[0080] As a result, the electrode according to Comparative Example 1 had a basis weight of approximately 22.6 mg / cm 2 The first density is 1.6 mg / cm 3 The first electrode layer 21 was formed so that the weight per unit area was about 38 mg / cm 2 The second density is 3.3 mg / cm 3 The second electrode layer 22 was formed so as to satisfy the following conditions.

[0081] In the electrode according to Comparative Example 2, the basis weight is about 22.6 mg / cm 2 The first density is 1.2 mg / cm 3 The first electrode layer 21 was formed so that the weight per unit area was about 38 mg / cm 2 The second density is 2.7 mg / cm 3 The second electrode layer 22 was formed so as to satisfy the following conditions.

[0082] In Comparative Example 1, the resistance value of the input / output performance was 146%, which was significantly increased compared to Example 1. The quick charging performance was 56 minutes, which was not a favorable result. On the other hand, the energy density was 685 Wh / L, which was a good result. In overall evaluation, a good electrode was not formed.

[0083] In Comparative Example 2, the resistance value of the input / output performance was 131%, which was significantly increased compared to Example 1. The quick charge performance was 28 minutes, which was a good result. The energy density was 542 Wh / L, which was not a good result. In overall evaluation, a good electrode was not formed.

[0084] (Results and Discussion) In Example 1, the densities of the first electrode layer 21 and the second electrode layer 22 can be controlled independently based on the manufacturing method according to the embodiment, so that the first density of the first electrode layer 21 can be set to 1.2 mg / cm3 as intended. 3 , the second density of the second electrode layer 22 is 3.3 mg / cm 3 Therefore, as described above, good rapid charging performance and energy density could be obtained. In addition, in Example 1, the second electrode layer was binderless, and the second electrode layer 22 was adhered to the first substrate 10 by the liquid bridging force when the electrolyte solution was applied, thereby obtaining good input / output performance.

[0085] On the other hand, in Comparative Example 1, the first electrode layer and the second electrode layer are pressed together, so the density of the second electrode layer is set to 3.3 mg / cm 3When the pressure applied to the first electrode layer is adjusted to 1.6 mg / cm, the pressing pressure of the first electrode layer is also increased, and the density of the first electrode layer is adjusted to 1.6 mg / cm. 3 This resulted in a significant increase in fast charging performance. In addition, the density of the first electrode layer was too high, which resulted in a high IV resistance and a decrease in input / output performance.

[0086] In Comparative Example 2, the density of the first electrode layer was set to 1.2 mg / cm3 in order to press the first electrode layer and the second electrode layer together. 3 When the pressure applied to the second electrode layer is adjusted to 2.7 mg / cm, the pressing pressure of the second electrode layer is reduced and the density of the second electrode layer is adjusted to 2.7 mg / cm. 3 This resulted in a significant drop in energy density. In addition, the low density of the second electrode layer meant that no conductive path was obtained, which resulted in a deterioration in IV resistance and a drop in input / output performance.

[0087] As described above, it has been confirmed that the manufacturing method based on this embodiment makes it possible to manufacture an electrode for a secondary battery that can increase the adhesion between the electrode layer and the substrate and improve the battery capacity and rapid charging performance.

[0088] The embodiments disclosed herein are illustrative and not restrictive in all respects. The scope of the present invention is defined by the claims, and includes all modifications within the meaning and scope of the claims. [Explanation of symbols]

[0089] 10 first substrate, 10a first main surface, 10b second main surface, 11 first metal foil, 12 second metal foil, 13 adhesive layer, 21 first electrode layer, 22 second electrode layer, 22a surface, 30 electrostatic screen device, 31 mixing tank, 32 supply section, 33 screen, 41 supply roller, 43, 44 press roller, 50 electrostatic screen device, 51 mixing tank, 52 supply section, 53 screen, 60 second substrate, 60a surface, 61 first roller, 62 second roller, 63 opposing roller, 71 transport roller, 80 electrolyte coating device, 100 electrode.

Claims

1. forming a first electrode layer at a first density on a first main surface of a first substrate; Providing a second electrode layer formed at a second density; laminating the prepared second electrode layer on a second main surface of the first base material; prior to the step of laminating the second electrode layer, applying an electrolyte solution to at least one of the second main surface of the first base material and a surface of the second electrode layer that will be in contact with the second main surface.

2. the step of preparing the second electrode layer includes a step of forming the second electrode layer on a surface of a second base material; and a step of pressing the second electrode layer formed on the surface of the second base material, The method for producing an electrode for a secondary battery according to claim 1 , wherein the laminating step includes a step of peeling the second electrode layer from the second substrate.

3. An endless intermediate transfer body is used as the second substrate, The method for manufacturing an electrode for a secondary battery according to claim 2 , wherein the step of laminating the second electrode layer includes a step of transferring the second electrode layer from the intermediate transfer body to the second main surface of the first substrate.

4. 4. The method for manufacturing an electrode for a secondary battery according to claim 3, wherein a first transport speed at which the first base material on which the first electrode layer is formed is transported toward a transfer position at which the second electrode layer is transferred is faster than a second transport speed at which the intermediate transfer body on which the second electrode layer is formed is transported toward the transfer position.

5. 5. The method for manufacturing an electrode for a secondary battery according to claim 1, wherein the first base material is a bonded body in which a first metal foil constituting the first main surface and a second metal foil constituting the second main surface are bonded together.

6. The method for producing an electrode for a secondary battery according to claim 1 , wherein the first electrode layer and the second electrode layer have different polarities.

Citation Information

Patent Citations

  • Bipolar electrode, method of manufacturing bipolar electrode, bipolar battery, battery pack and vehicle with these mounted thereon

    JP2005317468A

  • Negative electrode for lithium ion secondary battery and lithium ion secondary battery using the negative electrode

    JP2010238426A

  • Device and method for drying electrode material

    JP2011216227A

  • Manufacturing method of power storage device

    JP2015109205A

  • Power storage device

    JP2015164117A